PERSATUAN ALUMNI USM ORGANISES BALIKAMPUS PROGRAMME ON 29 AUGUST 2015 - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, 24 July 2015 Persatuan Alumni Universiti Sains Malaysia (USM) is organising a Balikampus Programme and is delighted to invite all former USM students to attend this reunion programme. Persatuan Alumni USM President, Professor Tan Sri Dzulkifli A. Razak said the Balikampus Programme is organised biennially at each odd year since 2003 to bring together USM alumni who are residing and working in Malaysia as well as abroad in a relaxed and friendly atmosphere.